EFEKTIVITAS PENYALURAN PROGRAM BANTUAN SOSIAL TUNAI (BST) DI MASA PANDEMI COVID-19 DI KELURAHAN KALABBIRANG KECAMATAN PATTALASSANG KABUPATEN TAKALAR) - Rahmah Indawati (Politeknik STIA LAN Makassar, 2022)
Effectiveness is the determining factor in achieving a predetermined goal or target in an agency, activity, or program is. The community's economy has suffered a lot as a result of the Covid-19 pandemic. The Cash Social Assistance Program aims to improve the well-being of the community and to help the community's economy recover from the Covid-19 pandemic. This study applied a descriptive qualitative approach. The data in this study were obtained from interviews, document review. There were eight informants of the study, consisting of the employee of the unproperous people division, the head of Kalabbirang Village and the employee of Kalabbirang Sub-District Data Section and five targeted receiver of cash social assistance. This study provided nine questions to government agencies regarding indicators of the effectiveness of distribution and five questions on monitoring the Cash Social Assistance program. The result of the study showed that implementation of the Cash Social Assistance program during the Covid-19 pandemic in Kalabbirang Village, Takalar Regency was effective and proceeded as planned. This nation is supported by a number of indicators, including the accuracy of program targets, achievement of program objectives, and programs monitoring that have been accomplished as planned. During the Covid-19 pandemic, the Takalar Regency and Kalabirang Village social service offices were active participants in the cash social assistance program in the Kalabirang Village.